Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles

Differential modulation in metabolites revealed with the improvement in the shelf-life of alphonso fruits - Dar, M. Saleem; Dholakia, Bhushan B.; Shanmugam, Haripriya; Gupta, Vidya S.; Subramanian, K. S.; Subramanian, J.; Giri, Ashok P. (Molecular Biotechnology, 2020)
Globally farmers have difficulty in extending the shelf-life of the tropical fruits due to their perishable nature. The present study aimed to assess the effect of hexanal nano-formulation treatment (NFT) on the shelf-life of Alphonso mango. Further, volatilomics was performed to explore the molecular basis of such effect. Untreated and treated fruits were sampled starting from 5th to 21st day after NFT at an interval of 4 days. Moderate changes in visual and digital colour parameters were evident from the intact and dissected fruits of NFT set compared to untreated fruits. Biochemical assays affirmed the phenotypic differences with significant changes in the colour imparting compounds like carotenoids and anthocyanins among them. Further, gas chromatography-mass spectrometry analysis revealed significant qualitative and quantitative variations in the different classes of compounds like lactones, furanones, esters, aldehydes and alcohols. Some of the key metabolites showed differential modulations among the NFT and untreated fruit sets indicating their potential role in various processes, which ultimately might have resulted in delayed ripening of the mango. Overall, this study has demonstrated the beneficial effect of hexanal and identified important metabolites with the enhanced shelf-life in Alphonso that could be useful for farmers and mango-based food/flavour industries.
Keywords: Alphonso; GC-MS; Metabolites; Nano-biotechnology; Nano-formulation; Shelf-life; Volatilomics